Pulmonary rehabilitation: history, promise and problems - Casaburi, Richard (Henry Stewart Talks, 2022)
The history of pulmonary rehabilitation, Pulmonary rehabilitation for COPD, Targets for improving exercise tolerance in pulmonary rehabilitation, The PROPEL study, Peter Lindenauer’s study, Therapies that improve mortality in COPD, Abysmal participation, Strategies to improve participation, Home-based rehabilitation